Graves′ orbitopathy: Management of difficult cases - Wiersinga, Wilmar M. (Medknow Publications & Media Pvt Ltd, 2012)
Management of Graves′ ophthalmopathy (GO) is based on three pillars: to stop smoking, to restore and maintain euthyroidism, and to treat the eye changes according to severity and activity of GO. Difficulties are frequently encountered in each of these three management issues. The advice to discontinue smoking is straightforward, but just a small minority of smokers is able to quit smoking. Detailed information on how smoking adversely affects the outcome of Graves′ disease may convince patients they have to stop smoking right away. Controversy exists on the most appropriate treatment of Graves′ hyperthyroidism in the presence of GO. 131I therapy is associated with a risk of about 15% for worsening of GO; a preventive course of steroids is indicated in the presence of risk factors (smoking, biochemically severe hyperthyroidism, high level of TSH receptor antibodies, active GO). Alternatives are thyroidectomy or long-term treatment with antithyroid drugs, which apparently are rather neutral with respect to the course of GO. Mild GO is not always perceived as being mild by the patients themselves. Selenium improves mild GO. Moderate-to-severe GO is preferably treated with intravenous methylprednisolone pulses, but serious side effects and relapsing GO do occur. After steroid failure combination therapy with low-dose oral prednisone with either cyclosporine or retrobulbar irradiation can be effective. Dysthyroid optic neuropathy is best treated with IV pulses, followed by orbital decompression if visual functions do not improve. In resistant cases, rituximab might be considered, although failures of this drug are also described.